Management and treatment of relapsed or refractory Ph(−) B-precursor ALL: a web-based, double-blind survey of EU clinicians. Issue 1 (December 2015) - Saltman, Deborah; Barlev, Arie; Seshagiri, Divyagiri; Katsoulis, Ioannis; Lin, Vincent; Barber, Beth
Abstract Background The prognosis for adult patients with Ph(-) B-precursor acute lymphoblastic leukaemia (ALL) who are refractory to treatment or experience relapse (R/R), is poor; over 90 % of these patients die from the disease, typically within a few months. While there are some national guidelines published for the treatment of adult patients with ALL, and local working group recommendations do exist, there is very little detail and no preferred treatment regimens for adult patients with R/R Ph(-) B-precursor ALL. The aim of this study was to describe current real-world clinical practice in Europe for the management and treatment of adult R/R Ph(–) B-precursor ALL. Methods A web-based, double-blind survey was conducted in November/December 2013 in France, Germany, Italy, Spain, and the UK. The survey was developed following consultation with specialist clinicians and a critical review of published literature. Eligible clinicians (15 per country) were board-certified in haemato-oncology or haematology; had at least 4 years of experience in their current role and had treated at least five patients with adult ALL in the 36 months before the survey, including at least one with R/R Ph(−) B-precursor ALL. Results Clinicians across the five countries consulted 16 guidelines and local working group recommendations for the diagnosis and treatment of R/R Ph(–) B-precursor ALL. Thirty three regimens for salvage therapy were reported; the most frequently cited was augmented hyper-CVAD (15 %), with vincristine the most commonly used agent. Salvage therapy regimens involved a range of agents, and most respondents reported using at least one cytotoxic agent; across respondents 10 different cytotoxic agents were cited. All respondents reported that toxicity was common for the regimens they used to treat R/R Ph(–) B-precursor ALL. Conclusions This study provides evidence of current management and treatment patterns of R/R Ph(–) B-precursor ALL in the real-world clinical practice in Europe. The approach to the treatment of R/R Ph(–) B-precursor ALL is heterogeneous, reflecting the lack of any clearly superior chemotherapeutic option, thus it appears that clinicians are trying a wide variety of therapies. These findings show a clear need for effective, tolerable treatments for R/R Ph(–) B-precursor ALL.